2013
DOI: 10.1002/clen.201300208
|View full text |Cite
|
Sign up to set email alerts
|

Water and Wastewater Treatment in Africa – Current Practices and Challenges

Abstract: Water and Wastewater Treatment in AfricaCurrent Practices and ChallengesSustainable access to safe drinking water and basic sanitation is an important part of the millennium development goals (MDGs). For most African countries, an extensive effort is needed for the last three remaining years for the achievement of the MDGs, especially in Sub-Saharan Africa. Current practices for water and wastewater treatment in Africa are insufficient to ensure safe water and basic sanitation. To address this challenge, joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 49 publications
2
90
0
3
Order By: Relevance
“…Sanitation in sub-Saharan African cities is dominated by pit latrines, septic tanks and other on-site solutions, many of which require attention to develop better systems for faecal sludge management. When it comes to sewer systems, infrastructure is lacking in most sub-Saharan African countries and sewer connections are limited [42]. For instance, in Addis Ababa the Kaliti treatment plant built in 1983 was designed to serve 50,000 people, but after 30 years serves only 13,000.…”
Section: Sanitation Requires Political Will and Dedicated Resourcesmentioning
confidence: 99%
“…Sanitation in sub-Saharan African cities is dominated by pit latrines, septic tanks and other on-site solutions, many of which require attention to develop better systems for faecal sludge management. When it comes to sewer systems, infrastructure is lacking in most sub-Saharan African countries and sewer connections are limited [42]. For instance, in Addis Ababa the Kaliti treatment plant built in 1983 was designed to serve 50,000 people, but after 30 years serves only 13,000.…”
Section: Sanitation Requires Political Will and Dedicated Resourcesmentioning
confidence: 99%
“…High turbidity, which decreases the quality of drinking water, is one of the major problems of sources of drinking water in Africa. For instance, in Nairobi, the turbidity of raw water can be 3 NTU in the dry season, and it may reach to 5000 NTU during the rainy season [17,18]. It is reported that the turbidity of Blue Nile and River Nile may reach 7,275 NTU and 6,575 NTU, respectively [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the use of decentralized water treatment systems has increased worldwide, but particularly in the developing world [1][2][3][4][5][6][7][8][9][10]. Due to their relatively small spatial scale and low carbon footprint, decentralized water filtration systems have a low environmental impact on water resources because they do not discharge effluent into waterways [4].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional water treatment often calls for complex multistage processes (namely coagulation, disinfection, flocculation, sand filtration, screen-filtration, ozonization, sedimentation) and requires a wide array of chemicals (namely chlorine, flocculents, hydrogen peroxide, lime, ozone). The processes therefore also typically require specialist expertise for installation and maintenance [4,[10][11][12][13]. As a result conventional wastewater treatment facilities are often expensive to install and maintain and have a high carbon footprint.…”
Section: Introductionmentioning
confidence: 99%